Construction 4.0: a survey of research trends - Perrier, Nathalie; Bled, Aristide; Bourgault, Mario; Cousin, Nolwenn; Danjou, Christophe; Pellerin, Robert; Roland, Thibaut (Journal of information technology in construction, 2020)
The fourth industrial revolution, called Industry 4.0, is transforming decision-making through the increasing use of information and digitization technologies. While Industry 4.0 is expanding rapidly in manufacturing industries, its induced transformations are gradually affecting other sectors, including the construction industry. In recent years, the use of 4.0 technologies in the construction industry, termed as ‘Construction 4.0’, has increased, mostly due to the immense potential of Industry 4.0 for improving the performance of construction projects and structuring their underlying management processes. This paper proposes a classification of existing literature on applications of Construction 4.0 technologies to allow for a better analysis of trends and gaps in the research. A total of nearly 200 research papers between 2009 and 2020 were reviewed and analyzed. Overall, the analysis shows that research on Construction 4.0 is closely aligned with the construction phase. Also, the most researched topics seem to be related to the management processes of quality, risk, and health and safety.